VEHICLE ROUTING PROBLEM ON JUICE DISTRIBUTION USING NEAREST NEIGHBOR METHOD - Tamyiz, Muchammad; Prasetyo, Waluyo (Universitas Nahdlatul Ulama Sidoarjo, 2018)
The problem of product distribution becomes an important topic in a company's transportation system. PT Amanah Prima Indonesia (API) is a national-scale company engaged in the production of juice drinks. With the number of consumers scattered in the Semarang area, it is necessary a solution in the distribution of products in order to obtain operational efficiency. The method used is Nearest Neighborhod Algorithm. The results obtained are: (a) Distance savings of 144.20 Km or 40.06%, (b) Product distribution time can be reduced for 5.15 hours or 30.31%, (c) Fuel costs used obtained cost savings of Rp.108.150, - or equal to 40.06%, (d) Expenses for driver and companion cost is no difference of Rp.600.000, -, and (f) The total cost of distribution is obtained savings of Rp. 108,150 or 12.43%.